Alternative water resources quality assessment during flood disaster in Kuala Krai, Kelantan, Malaysia - Koh, Liew See; Nasir Nayan; Mohmadisa Hashim; Yazid Saleh; Hanifah Mahat (Penerbit Universiti Kebangsaan Malaysia, 2021)
Quality assessment of water resources is important to ensure the well-being of residents, especially the victims who are affected by floods and having difficulties in obtaining clean water supply when the floods hit. This paper seeks to discuss the quality assessment of water resources in the district of Kuala Krai, Kelantan. Field methods were used to collect water samples during the northeast monsoon season in the month of December 2016/January 2017 involving six well stations, four flood water stations and four rainfall stations. The quality assessment of water resources involved six key parameters, namely DO, pH, BOD, COD, NH3 N and SS using the Water Quality Index (WQI) analysis. The results of the analysis showed that the WQI percentage of well and flood water stations accounted for 61.31 to 75.95% which is Class III of moderately contaminated status, except the T6 station that recorded 80.99% of WQI value which is Class II of good status. The findings also showed that all WQI values from the rainwater stations were at 87.85 to 89.10%, which is Class II of good status. This condition explains that the rainwater resources have better quality than the well and flood water resources. With the help of this research, the flood manager’s party can take systematic management measures in ensuring that flood victims receive water supplies during flood events. In this regard, infectious diseases resulted from the consumption of contaminated water among flood victims can be reduced.